The Impact of Influencer Marketing on Halal Product Purchase Decisions: An Analysis in the Digital Era - Nanda Alfreda Putri; Mariyatul Kiptiyah; Revalina Aurelia Oktanti; Shabahah El Rojana; Syarifuddin Hidayatullah; Aldi Khusmufa Nur Iman (Penerbit Hellow Pustaka, 2025)
This study aims to understand the impact of influencer marketing strategies on consumer attitudes in choosing halal products in the digital era. The approach used was a systematic literature review, examining 15 relevant journal articles from both Indonesia and abroad. The study results show that marketing through influencers has a significant positive influence on halal product purchase decisions, especially when the influencers are trusted and their values ​​align with the consumer's religious principles. Furthermore, other factors such as electronic word of mouth (e-WOM), content marketing, and brand image have also been shown to strengthen consumer purchase intentions. These findings emphasize the importance of an integrated digital strategy, where the choice of social media platform, the relevance of religious values, and the combination with other digital marketing strategies determine campaign effectiveness. Practically, this study provides recommendations for businesses to utilize influencers who align with the characteristics of Muslim consumers, optimize educational content, and develop honest, transparent, and ethical marketing communications in accordance with Sharia principles.